Appropriateness of Admission to General Medical-Surgical ICUs in a University Teaching Hospital - Rowan M. Abuyadek; Hoda Z. Helmy; Akram M. Fayed; Moataza M. Abdel Wahab; Dina H. Fouad (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Resource allocation and increased cost of critical care services have been a global concern. Intensive care unit (ICU) admission is usually reserved for patients with reversible medical conditions who have a reasonable probability of substantial recovery. The admission process to ICU shows considerable variations, and it is difficult to assess the appropriateness of decision prospectively for ethical and legal reasons. However, data regarding ICU admission would help health managers to make decisions concerning healthcare facilities planning and administration. The study aim was to assess the appropriateness of admission to ICU. Materials and Methods The study was conducted in two general medical-surgical ICUs in university teaching hospital. Appropriateness of admission was approached through assessment of adherence to guidelines of ICU admission recommended by Society of Critical Care Medicine, severity of illness of admitted patients using Acute Physiology and Chronic Health Evaluation II score, utilization of ICU specific treatment in the first 24 hours of admission, and mechanical ventilation during ICU stay. Results Among 324 patients admitted in 2013–2014, almost all of them (99.4%) were adherent to diagnosis model of Society of Critical Care Medicine (SCCM) guidelines for ICU admission and approximately 75% were adherent to objective parameters model of SCCM guidelines. Mean Acute Physiology And Chronic Health Evaluation II score on admission was 13.84 point. About 18% of patients did not receive ICU specific interventions in the first 24 hours of admission to ICU. In addition, about 36% of sample patients did not receive mechanical ventilation during their ICU stay. ICU mortality reached 39.8% of the sample. Discussion Guidelines recommended by SCCM are straightforward and easy to use and are used to make quick decisions regarding admission. Need for ICU specific interventions in the first 24 hours of admission is crucial in assessment of ICU admission. Mechanical ventilation is the most important ICU specific intervention; appropriateness can be assessed depending on the need for mechanical ventilation.